Risiko Reaktivasi Tuberkulosis Laten pada Terapi COVID-19 - Abas, Ghina Mutiara; Sjatha, Fithriyah; Rosana, Yeva (Fakultas Kedokteran Universitas Trisakti, 2023)
The high mortality rate among COVID-19 patients in the acute respiratory distress syndrome (ARDS) phase led to the administration of immunosuppressive drugs. Corticosteroids could block inflammation caused by cytokine storm, and prevent pneumonia, edema, fibrosis, and ARDS. Even though it was believed to have beneficial effects, corticosteroids can suppress T CD4+ and CD8+ cell-mediated immunity reaction through decreased IFNγ production thus leading to reactivation of latent Tuberculosis (LTBI). Therefore, the usage of corticosteroids in the ARDS phase of COVID-19 patients should be carefully given; pre-screening of LTBI may be done to avoid Tuberculosis reactivation.